PRODUCER SOCIAL RESPONSIBILITY: DEPOSIT-RETURN SYSTEM - Tarayevska, Lesia; Kornaga, Diana; Haliuk, Iryna (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and applied foundations of producer social responsibility in the context of implementing the concept of Extended Producer Responsibility (EPR) and developing a circular economy model. The study substantiates that modern business responsibility should extend beyond economic performance and include environmental, social, and ethical obligations related to the entire life cycle of products. Particular attention is paid to the deposit return system (DRS) as an effective mechanism for implementing the environmental component of producer responsibility and stimulating sustainable consumption practices.The paper analyzes the European experience of implementing deposit return systems, particularly in Germany, Norway, Lithuania, and Estonia, where high return rates for packaging waste have been achieved through automated collection systems, digital logistics, and active stakeholder engagement. It is established that the effectiveness of DRS depends on legislative support, consumer motivation, developed infrastructure, digital technologies, and the integration of producers into waste management processes. The research identifies the key barriers to implementing a deposit return system in Ukraine under current wartime and post-war conditions. These challenges include social and behavioral barriers, insufficient infrastructure, energy instability, financial risks, and low adaptation of existing recycling mechanisms to circular economy principles. Based on the conducted analysis, the author proposes adaptive approaches to the modernization of the Ukrainian DRS model, including hybrid collection systems, QR-based identification technologies, digital cashback integration, eco-modulation of deposits, and the creation of energy-autonomous collection points. The article also presents the results of an empirical survey that demonstrates a relatively high level of public readiness to participate in deposit-based recycling systems, especially among young people and students. The findings confirm that environmental awareness and convenient digital payment mechanisms significantly influence consumer willingness to support circular economy initiatives. The practical significance of the study lies in the possibility of using the proposed approaches in the development of state environmental policy, regulatory frameworks for EPR implementation, and strategies aimed at transitioning Ukraine toward a sustainable circular economy aligned with European environmental standards.